2014
DOI: 10.1007/s13197-014-1351-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality attributes and consumer acceptance of new ready-to-eat frozen restructured chicken

Abstract: The aim of the present study was to develop a new restructured product, cooked and frozen ready-to-eat product that was prepared with boneless chicken meat (breast and drumstick) and mechanically separated chicken meat (MSCM). Non-meat ingredients, such as transglutaminase (TG) and egg albumin powder, were tested to obtain a better strength of adhesion between the meat particles. Five formulations for restructured chicken were developed as follows: T1 (1 % transglutaminase), T2 (1 % transglutaminase and 15 % M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…The available technologies[1] are able to provide microbiologically safe food products having high nutritional quality, similarly to the corresponding fresh product. Consequently, since they do not need any other treatment before being eaten, fresh-cut vegetables can be considered as ready-to-eat products (de Almeida et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The available technologies[1] are able to provide microbiologically safe food products having high nutritional quality, similarly to the corresponding fresh product. Consequently, since they do not need any other treatment before being eaten, fresh-cut vegetables can be considered as ready-to-eat products (de Almeida et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…was not detected on the samples, while the coagulase-positive Staphylococcus count was < 10 2 CFU g -1 , and the Coliforms at 45 ºC were < 3 MPN g -1. Similarly, Almeida et al (2015) reported an expected microbiological quality for chicken nuggets (Resolução RDC n. 12, 2001).…”
Section: Microbiological Parametersmentioning
confidence: 95%
“…A P-50 probe (long shaft, regular base) was used to perform a two-cycle compression test on the sample. The sample was compressed by the probe to 30% at a speed of 1 mm s −1 , and the initial force was set to 0.5 N [17].…”
Section: Determination Of Microcapsule's Properties 241 Thermogravime...mentioning
confidence: 99%